SPECIFIC CHALLENGES OF SMALL BUSINESS UTILIZATION IN HEALTH CARE - NAZAROVA, SHAXNOZA (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article reveals the specific aspects of the problems of using small business in the health sector. The role of small business in ensuring the effectiveness of the budget system is analyzed. Specific features of the relationship between the budget system and small business are expressed.